Taking sides : (McGraw-Hill/Dushkin, 2006)
Taking Sides: Clashing Views on Controversial Issues in Physical Anthropology , 1/e presents current controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. Each issue is thoughtfully framed with an issue summary, an issue introduction, and a postscript. An instructor's manual with testing material is available for each Taking Sides volume.